Pemanfaatan Limbah Penambangan Bukit Kapur Untuk Stabilisasi Tanah Lempung ( Clay ) - Enita Suardi; Zulfira Mirani; Silvianengsih Silvianengsih; Oni Guspari; Desmon Hamid (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2021)
Soil stabilization by adding new materials is one of the alternatives to soil repair that can improve the properties of the soil, namely by mixing new materials and soil that is then compacted. Waste left over limestone hill mining,among others in the form of materials with various sizes of granules. This study aims to review the effect of the addition of limestone hill mining waste material on the density and value of the California Bearing Ratio (CBR) of clay soil. Tests conducted only on a laboratory scale with variations in the increase in limestone hill mining waste levels are 0%, 5%, 10%, and 15% to the total weight of the mixture. Laboratory CBR testing is performed under optimum water content conditions. The results showed that the stabilization of soft soils using limestone hill mining waste, can increase the density and value of soil CBR. The most optimal level of use of limestone hill mining waste and which provides the highest CBR value is for the addition of 5%of limestone hill mining waste with a CBR value of 26.5%.